Reduced risk of severe COVID-19 with lithium use: a large-scale comparison with valproate users and other COVID-19 patients - Avni, Chen; Blasbalg, Uri; Toren, Paz (Frontiers in Psychiatry, 2026)
BackgroundLithium, a commonly used mood stabilizer with immunomodulatory and antiviral properties, has been hypothesized to lessen the severity of COVID-19, but population-level evidence remains limited.MethodsIn this retrospective cohort study, we examined electronic health records from over 1.49 million adults with confirmed COVID-19 in Israel between March 2020 and November 2021. Individuals were categorized based on sustained use of lithium (n=857), valproate (n=5,302), or no exposure to either medication. Severe COVID-19 was defined as hospitalization, respiratory support, extracorporeal membrane oxygenation, or death. To account for baseline differences, we applied inverse probability weighting and logistic regression with correction for rare events.ResultsLithium use was associated with significantly lower odds of severe COVID-19, even though users were older and had more medical comorbidities. In contrast, valproate use was linked to increased risk.ConclusionThese findings suggest that lithium may provide a protective effect against severe COVID-19 outcomes, independent of underlying vulnerability, and support further investigation into the broader health implications of psychotropic medications.